The child's theory of mind - Wellman, Henry M. (A Bradford Book, 1990)
Children, theories, and the mind: An introduction Understanding the basic distinction between mental and physical phenomena Young children's understanding of belief Commonsense belief-desire psychology Everyday theories Young children's belief-desire psychology Further clarifications of the theory and the data Before three From three to six: From copies to imaginings to interpretations From three to six: Other implications Beyond six